SENI TRADISIONAL BANTENGAN DI DUSUN BORO PANGGUNGREJO GONDANGLEGI MALANG: SEBUAH KAJIAN ETNOGRAFI - Amir Faris; Ahmad Khoyyum; Ita Uzzulaifatit Thoriqoh; Latifatun Nisak (Jurnal Penelitian Ilmiah INTAJ, 2017)
Bantengan is an Indonesian folk performing art. Bantengan is a performance art that combines elements of martial arts, dances, kanuragan, music, and magical spell. Bantengan has spread in Indonesia, especially in East Java hinterland. One of them is in the hamlet of Boro Panggungrejo Gondanglegi Malang. However, there are some changes and shifts due to changes of time. One of the changes occurred in the "trance" of the players. Current bantengan players seem to show Pretending "trance". In addition, they get trance without the handler, so it is difficult to set up and control. Based on this background, the research explores two points; (1) public attitudes of Boro Panggugrejo Gondanglegi Malang over Bantengan; (2) Bantengan impacts on the society of Boro Panggungrejo Gondanglegi Malang. This study is a qualitative field research. The type used in this research is descriptive-ethnographic. The results of this study indicate that the traditional art Bantengan in Boro Panggungrejo Gondanglegi Malang is a folk art that aims to accommodate brutal, those who become substation residents at day and night, to be directed at better activities. In addition, tradi-tional art Bantengan also be interpreted as a forum to facilitate interaction (silaturrahmi) among local residents and the wider community. Traditional art Bantengan also be a forum to discuss issues relating to the development of the hamlet or village. Bantengan traditional art has positive impacts to society in Boro Panggungrejo Gondang-legi Dusun Malang. Through Bantengan, a servant relationship with his Lord (habl min AllÄh) will be close through prayer, istighatsah and khatm Qur'an which became one of requirements that must be met by the players of bantengan. So is the relationship between humans (habl min al-nÄs). Bantengan traditional art open alternative earning for the people, encourage gotong-royong and care for others. However, bantengan also has negative impacts, for example disrupting public roads, disrupting rest time when Bantengan does exercise in the evening. As for the players, they must avoid an unstable mental atmosphere because they will be easy get trance.